A novel hybrid linear-hyperbranched poly(butylene adipate) copolymer as an epoxy resin modifier with toughening effect - Shiravand, Fatemeh; Ascione, Laura; Persico, Paola; Carfagna, Cosimo; Brocks, Thatiane [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Puglisi, Concetto; Samperi, Filippo; Ambrogi, Veronica (Wiley, 2016)
A study was carried out on the effect of a hybrid linear-hyperbranched poly(butylene adipate) copolymer on the properties of a commercial epoxy resin. First, the synthesis of the hyperbranched systems was optimized. These systems were obtained by reacting linear oligomers with 1,1,1-tris(hydroxymethyl)propane used as branching agent and varying the reaction times from 16 to 44 h. The synthesized samples were characterized through matrix-assisted laser desorption ionization time-of-flight mass spectrometry, differential scanning calorimetry and thermogravimetric analysis. Results showed that for reaction times of 30 h a highly branched system, namely 5HB30, was obtained. This system was chosen as toughening agent for a commercial high-performance epoxy resin. A kinetics analysis of epoxy/5HB30 blends indicated that the hyperbranched system had no accelerator or catalytic effect on the crosslinking reaction in the resin. Furthermore, it was demonstrated that 5HB30 acted as an excellent toughening agent, increasing significantly impact resistance up to 90% with respect to neat epoxy resin. The toughness behaviours of epoxy-based blends were explained by investigating the fracture surface after impact tests through scanning electron microscopy before and after solvent etching. It was observed that the globular-like hyperbranch-rich domains, dispersed throughout the continuous epoxy resin, were able to absorb the impact energy without affecting thermal stability.
Keywords: Curing kinetics; Epoxy resins; Hyperbranched polymers; Toughening